Parasite and host kinases as targets for antimalarials. (1st February 2023) - Ong, Han Wee; Adderley, Jack; Tobin, Andrew B.; Drewry, David H.; Doerig, Christian
ABSTRACT: Introduction: The deployment of Artemisinin-based combination therapies and transmission control measures led to a decrease in the global malaria burden over the recent decades. Unfortunately, this trend is now reversing, in part due to resistance against available treatments, calling for the development of new drugs against untapped targets to prevent cross-resistance. Areas covered: In view of their demonstrated druggability in noninfectious diseases, protein kinases represent attractive targets. Kinase-focussed antimalarial drug discovery is facilitated by the availability of kinase-targeting scaffolds and large libraries of inhibitors, as well as high-throughput phenotypic and biochemical assays. We present an overview of validated Plasmodium kinase targets and their inhibitors, and briefly discuss the potential of host cell kinases as targets for host-directed therapy. Expert opinion: We propose priority research areas, including (i) diversification of Plasmodium kinase targets (at present most efforts focus on a very small number of targets); (ii) polypharmacology as an avenue to limit resistance (kinase inhibitors are highly suitable in this respect); and (iii) preemptive limitation of resistance through host-directed therapy (targeting host cell kinases that are required for parasite survival) and transmission-blocking through targeting sexual stage-specific kinases as a strategy to protect curative drugs from the spread of resistance.